Strategies for fabrication of highly-dense ordered arrays of metal microdisks by the scanning electrochemical microscopy microwriting approach - Brites Helú, Mariela Alicia (2017)
The microwriting approach of the scanning electrochemical microscopy (SECM) was adapted and optimized for the fabrication of extensive ordered arrays of gold microdisks deposited on conductive supports. This technique uses a SECM tip as a source for the localized delivery of metal ions by well-controlled electro-dissolution of the metal microelectrode. In this work, novel configurations of recessed-microelectrode tips (radii ≤ 12.5 μm) were developed to make possible the deposition of a large number of well-defined disks from the same probe by a semi-automatic procedure. A sequence of steps that coordinates tip potential, tip position, and substrate potential values was designed and implemented to improve the repeatability and confinement of the deposited microdisks. The effects of potential and time conditions for gold electro-dissolution and electrodeposition on the morphological properties of gold disks deposited on Pt and glassy carbon were explored. The selective modification of glassy carbon-supported gold arrays with an electrocatalytic material (Pt) for a specific reaction (hydrogen evolution) and their further SECM activity screening were described to illustrate a way to use them as multielectrode platforms.